(untitled) (The Research of Medical Science Review, 2025)
Cancer biomarker and mediators are driving tools of tumorigenic pathways. Breast carcinoma is the most frequently diagnosed cancer among women, it possesses the highest incidence approximately 26% of all cancers. The review aims to remove and confront logical fallacies improvised for breast cancer cell, additionally excavating the insights into the therapeutically targeted biomarkers for the breast cancer eradication. The signaling cascades induce down streaming of pro-apoptotic mediators such as Cytochrome C, FAS L, Bak/ Bax, Lamin B. The functional coordination of cellular apoptotic and proliferative pathway includes tumor agonists (FAIM1, 2, 3), PKcs, LCL161, Bcl2 & Bcl-xL, PKA, MAPK & PKB e.tc, playing legitimate role in oncogenesis. Granzyme B cytotoxically increased in malignant /proliferative breast tumor cases, indexing high CD8 and TIL activation. Next the cytotoxic granule arbitrated route is Fas R/ FasL, in prosurvival route is FAIM-L, FAIM2 may interfere CD95/ CD95L in the presence of XIAP (anti-apoptotic protein). The complications in cancer advancement can be trekked if the weapons in cancer treatment and strategies that take benefit of cancer cell’s “Achille’s heels”, are identified. Conclusively the review will converge the gaps regarding exploitation and prediction of cancer markers. Documenting the forthright biomarkers will provide significant and novel milestones for breast cancer diagnosis and prognosis in clinical oncology.